A Framework for Assessing Scientific Merit in Ethical Review of Clinical Research. Issue 2 (20th March 2019) - Binik, Ariella; Hey, Spencer Phillips
ABSTRACT: Ethics guidelines and commentary suggest that a central function of research ethics committees is to assess the scientific merit of the protocols they review. However, some commentators object to this role, and evidence suggests that the assessment of scientific merit is a significant source of confusion and animosity between ethics committees and clinical investigators. In this essay, we argue that ethics committees should assess the scientific value and validity of research protocols and that new decision‐making tools are needed to help them do so in a systematic, transparent, and reliable way. We present a novel ethical framework that can assist in this task.